Trends of Active Learning in Higher Education and Students’ Well-Being: A Literature Review - Ribeiro-Silva, Elsa; Amorim, Catarina; Aparicio-Herguedas, José Luis; Batista, Paula (Frontiers in Psychology, 2022)
This is a literature review which main purpose was to inspect how the use of active learning methodologies in higher education can impact students’ well-being. Considering the Heads of State meeting at United Nations Headquarters on September 2015, in which the 2030 Agenda for Sustainable Development was adopted by all United Nations Member states, this literature review is limbered to the time period between September 2015 and September 2021. A previous research focused on reviews was made to support the conceptual framework. The search was done in two databases - Web of Science main collection and Scopus - by two researchers autonomously, using the following search criteria: “higher education AND active learning AND student AND wellness OR well-being OR wellbeing”. The studies section attended the following inclusion criteria: (i) published in peer-reviewed journals; (ii) empirical studies; (iii) written in English, French, Portuguese or Spanish; (iv) open access full text; (v) Higher education context; and (vi) focused on the topic under study. The search provided 10 articles which were submitted to an inductive thematic analysis attending to the purpose of this review, resulting in two themes: (i) students’ well-being during confinement; (ii) methodological solutions for students’ well-being. Data show that the use of active methodologies, as digital technologies, and the incorporation of some practice as physical activity and volunteering seems to benefit students’ well-being, namely in their academic achievement, physical, emotional, and social life, and empower them to the professional future with multi-competencies. Higher education institutions need to understand the value of active learning methodologies in sustained education and promote them in their practices.